Tumors overexpressing RNF168 show altered DNA repair and responses to genotoxic treatments, genomic instability and resistance to proteotoxic stress - Chroma, K; Mistrik, M; Moudry, P; Gursky, J; Liptay, M; Strauss, R; Skrott, Z; Vrtel, R; Bartkova, J; Kramara, J; Bartek, J (Oncogene, 2017)
Chromatin DNA damage response (DDR) is orchestrated by the E3 ubiquitin ligase ring finger protein 168 (RNF168), resulting in ubiquitin-dependent recruitment of DDR factors and tumor suppressors breast cancer 1 (BRCA1) and p53 binding protein 1 (53BP1). This ubiquitin signaling regulates pathway choice for repair of DNA double-strand breaks (DSB), toxic lesions whose frequency increases during tumorigenesis. Recruitment of 53BP1 curbs DNA end resection, thereby limiting homologous recombination (HR) and directing DSB repair toward error-prone non-homologous end joining (NHEJ). Under cancer-associated ubiquitin starvation conditions reflecting endogenous or treatment-evoked proteotoxic stress, the ubiquitin-dependent accrual of 53BP1 and BRCA1 at the DNA damage sites is attenuated or lost. Challenging this current paradigm, here we identified diverse human cancer cell lines that display 53BP1 recruitment to DSB sites even under proteasome inhibitor-induced proteotoxic stress, that is, under substantial depletion of free ubiquitin. We show that central to this unexpected phenotype is overabundance of RNF168 that enables more efficient exploitation of the residual-free ubiquitin. Cells with elevated RNF168 are more resistant to combined treatment by ionizing radiation and proteasome inhibition, suggesting that such aberrant RNF168-mediated signaling might reflect adaptation to chronic proteotoxic and genotoxic stresses experienced by tumor cells. Moreover, the overabundant RNF168 and the ensuing unorthodox recruitment patterns of 53BP1, RIF1 and REV7 (monitored on laser micro-irradiation-induced DNA damage) shift the DSB repair balance from HR toward NHEJ, a scenario accompanied by enhanced chromosomal instability/micronuclei formation and sensitivity under replication stress-inducing treatments with camptothecin or poly(ADP-ribose) polymerase (PARP) inhibitor. Overall, our data suggest that the deregulated RNF168/53BP1 pathway could promote tumorigenesis by selecting for a more robust, better stress-adapted cancer cell phenotype, through altered DNA repair, fueling genomic instability and tumor heterogeneity. Apart from providing insights into cancer (patho)biology, the elevated RNF168, documented here also by immunohistochemistry on human clinical tumor specimens, may impact responses to standard-of-care and some emerging targeted cancer therapies.
Keywords: mutageny; nádorové buněčné linie; signální transdukce; DNA Damage; transport proteinů; nestabilita genomu; regulace genové exprese u nádorů; Ubiquitin; poškození DNA; oprava DNA spojením konců; Signal Transduction; Amino Acid Motifs; mutace; Carcinogenesis; Cell Line, Tumor; ubikvitinligasy; aminokyselinové motivy; fenotyp; Mutagens; 53BP1; Phenotype; Ubiquitin-Protein Ligases; ubikvitin; Mutation; Humans; Gene Expression Regulation, Neoplastic; homeostáza; oprava DNA; Genomic Instability; Protein Transport; DNA End-Joining Repair; DNA Repair; Homeostasis; karcinogeneze; Tumor Suppressor p53-Binding Protein 1; lidé